Increased α-synuclein phosphorylation and oligomerization and altered enzymes in plasma of patients with Parkinson’s disease - Yin, Na; Li, Pengjie; Li, Xuran; Li, Xin; Wang, Yiming; Yu, Xiaohan; Deng, Yeyun; Wang, Chaodong; Yu, Shun (Neuroscience, 2025)
•PD plasma promotes α-syn phosphorylation and oligomerization.•α-syn phosphorylation and oligomerization rates are higher in PD than in HC plasma.•Levels of enzymes regulating α-syn phosphorylation is altered in PD plasma.•α-syn phosphorylation and oligomerization rates discriminate PD patients from HCs. The brain of patients with Parkinson’s disease (PD) was characterized by increased phosphorylation and oligomerization of α-synuclein (α-syn) and altered activity of enzymes regulating α-syn phosphorylation and oligomerization. Whether increased α-syn phosphorylation and oligomerization as well as related enzyme changes can be detected in the plasma of PD patients remains unclear. Here, we showed that human α-syn proteins incubated in PD plasma formed more oligomerized α-syn (O-α-syn) and phosphorylated α-syn (pS-α-syn) than those in healthy control (HC) plasma. Receiver operating characteristic (ROC) curve indicated that α-syn oligomerization rate and phosphorylation rate discriminated PD patients well from HC subjects. Moreover, they were both positively correlated with Hoehn and Yahr staging and polo-like kinase 2 (PLK2, an enzyme promoting α-syn phosphorylation) levels, and negatively correlated with protein phosphatase 2A levels (PP2A, an enzyme dephosphorylating α-syn) and glucocerebrosidase (GCase, an enzyme whose deficiency causes α-syn oligomerization) activity and ceramide (a product of GCase and a natural PP2A activator) levels. The above results suggest that increased α-syn oligomerization and phosphorylation rates and related enzyme changes can be detected in PD plasma and used to discriminate PD patients from HC subjects and predict PD progression.